Institutional Manpower Retraining Programs: A Case Study - Lancashire, Jane Margaret (My University, 1976)
This is the report of a study of trainees enrolled in an institutional occupational retraining program supported under the Adult Occupational Training Act. Since the early 1960's, institutional job retraining programs have grown to become a major vehicle for absorbing the jobless in times of high unemployment and for supplying employers' increasing demands for inexpensive pools of labor when production is resumed. In particular, this study focuses on the means by which the job training center, as a resocialization organization, prepares individuals for the employee role. We examine retrainees' attitudes toward acquiring job skills and on changes in their levels of assimilation of those worker attributes viewed as desirable by employers. The findings show that such background factors as social class origin, the respondent's prior occupation, formal educational attainment, and sex affect variations in the resocialization experience. While most research on manpower programs has addressed itself to the issue of estimating the economic benefits of training programs, our research on the orientations of trainees investigates an area that has received little attention. This research is an exploratory study. Viewed in the broadest context, it deals with one aspect of the problem, of poverty and its sources in the structure and ideology of present day capitalistic society.
Keywords: Sociology; Sociology